Trinidad Country Club, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
A painting of the Trinidad Country Club show the driveway leading to the main entrance of the building and automobiles parked on the front lawn. The postcard is addressed to Miss Pearl Fountain, Maryland, U.S.A. Affixed to the postcard is a Trinidad and Tobago 12 cents stamp. Postcard number 77760.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Clubs--Trinidad and Tobago; Driveways--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Trinidad Country Club